Perovskite solar cell, preparation method thereof and photovoltaic module

By introducing a layer of silver nanoparticles as crystal nuclei into perovskite solar cells, the crystallization of the perovskite absorption layer and light reflection are promoted, thus solving the problems of crystallization quality and light utilization efficiency of perovskite solar cells and achieving a high-efficiency improvement in photoelectric performance.

CN121174789APending Publication Date: 2025-12-19CHINT NEW ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410793262.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-19
Publication Date
2025-12-19

AI Technical Summary

Technical Problem

How to improve the crystal quality of perovskite solar cells, reduce defect density, and enhance photoelectric performance?

Method used

Using a layer of silver nanoparticles as crystal nuclei promotes the crystallization of the perovskite absorption layer, forming a high-quality perovskite film with large grain size and low defect density. The light-trapping structure is formed through the reflection effect of the silver nanoparticle layer to improve the light utilization rate.

Benefits of technology

This significantly improves the photoelectric performance of perovskite solar cells, enhancing open-circuit voltage, short-circuit current, and photoelectric conversion efficiency, and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121174789A_ABST
    Figure CN121174789A_ABST
Patent Text Reader

Abstract

The invention provides a perovskite solar cell, a preparation method thereof and a photovoltaic module, and the perovskite solar cell comprises a substrate, a first carrier transmission layer, a perovskite absorption layer, a second carrier transmission layer and an electrode layer which are sequentially stacked. And a nano-silver particle layer is arranged between the first carrier transport layer and the perovskite absorption layer. According to the invention, the nano-silver particle layer is used as a crystal nucleus, so that the crystallization of the perovskite absorption layer is promoted, and the high-quality perovskite thin film with large grain size and low defect density is formed; in addition, the particle surface of the nano-silver particle layer can reflect sunlight, a light trapping structure is formed, and the utilization rate of light can be remarkably improved. In conclusion, the photoelectric property of the perovskite solar cell can be effectively improved, and the perovskite solar cell has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solar cell material technology, specifically relating to a perovskite solar cell, its preparation method, and a photovoltaic module. Background Technology

[0002] With the continuous development of human society, the demand for energy is increasing. Traditional energy sources, such as oil, natural gas, and coal, are non-renewable. Not only are their reserves dwindling, but they also cause significant environmental pollution. Therefore, vigorously developing renewable, green, and clean energy sources is extremely urgent and important. Among these, solar energy stands out. Solar energy is inexhaustible and does not harm the environment. Consequently, its application research has received increasing attention, and developing clean, pollution-free solar energy with vast reserves has become a hot topic of research for scientists.

[0003] In recent years, metal halide perovskite materials have attracted increasing attention due to their unique properties, such as low excitation energy, long carrier diffusion length, tunable band structure, and high carrier mobility. Through optimization of deposition methods, interface engineering techniques, and transport layer materials, perovskite solar cells (PSCs) have achieved a significant increase in power conversion efficiency (PCE) from 3.8% to 26.1% over the past decade. To achieve high-performance PSCs, improving the crystallinity of perovskite is one of the main ways to enhance the intrinsic properties of the crystal, thereby reducing defect sites and non-radiative recombination, which in turn improves the open-circuit voltage (Voc) and carrier transport capability of the cell.

[0004] In typical PSCs, the perovskite layer lies between the hole transport layer (HTL) and the electron transport layer (ETL), realizing an inverse pin or formal nip structure. For mesoporous structures, the ETL contains a mesoporous layer, which facilitates the extraction of electrons from the active layer and acts as a crystal scaffold to promote perovskite crystal growth. The perovskite absorber layer has a significant impact on battery performance, especially the morphology and crystallinity of the perovskite layer, which are crucial for achieving better device performance. However, crystal defects present on the film surface and at grain boundaries can lead to the formation of trapped states, causing nonradiative recombination.

[0005] Therefore, how to improve the crystallization quality and obtain a high-quality perovskite absorber layer with large grain size and low defect density is a key issue that urgently needs to be studied. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the present invention aims to provide a perovskite solar cell, its fabrication method, and a photovoltaic module. This invention uses a layer of silver nanoparticles as crystal nuclei, thereby promoting the crystallization of the perovskite absorber layer and forming a high-quality perovskite thin film with large grain size and low defect density. Furthermore, the surface of the silver nanoparticles can reflect sunlight, forming a light-trapping structure that significantly improves light utilization. In summary, this invention can effectively improve the photoelectric performance of perovskite solar cells and has broad application prospects.

[0007] To achieve this objective, the present invention adopts the following technical solution:

[0008] In a first aspect, the present invention provides a perovskite solar cell, the perovskite solar cell comprising a substrate, a first carrier transport layer, a perovskite absorber layer, a second carrier transport layer and an electrode layer stacked sequentially, wherein a layer of silver nanoparticles is disposed between the first carrier transport layer and the perovskite absorber layer.

[0009] This invention uses a layer of silver nanoparticles as crystal nuclei to promote the crystallization of the perovskite absorber layer, forming a high-quality perovskite thin film with large grain size and low defect density. Furthermore, the surface of the silver nanoparticles can reflect sunlight, forming a light-trapping structure that significantly improves light utilization. In summary, this invention can effectively improve the photoelectric performance of perovskite solar cells and has broad application prospects.

[0010] In a preferred embodiment of the present invention, the substrate is transparent conductive glass.

[0011] The present invention does not limit the material of the transparent conductive glass. For example, it can be ITO (indium tin oxide) or FTO (fluorine-doped tin oxide).

[0012] Preferably, the material of the electrode layer includes any one of Al, Au, Ag or carbon.

[0013] As a preferred embodiment of the present invention, the nano-silver particle layer comprises silver cubic nanoparticles.

[0014] Preferably, the side length of the silver cube nanoparticles is 10-150 nm, for example, it can be 10 nm, 50 nm, 100 nm or 150 nm.

[0015] In this invention, if the side length of the silver cubic nanoparticles is too small, although the light utilization rate is greatly improved, it cannot promote the crystallization of the perovskite film, resulting in a decrease in film quality and a decrease in battery efficiency; if the side length of the silver cubic nanoparticles is too large, it may hinder the extraction of charge carriers inside the battery, thereby affecting battery efficiency.

[0016] Preferably, the thickness of the nano-silver particle layer is 10-300nm, for example, it can be 10nm, 50nm, 100nm, 150nm, 200nm, 250nm or 300nm, etc.

[0017] In this invention, the particles in the silver nanoparticle layer may be stacked, resulting in a layer thickness greater than the side length of the silver cubic nanoparticles.

[0018] As a preferred embodiment of the present invention, the first carrier transport layer and the second carrier transport layer transport carriers of opposite types.

[0019] It should be noted that if the first carrier transport layer is an electron transport layer, then the second carrier transport layer is a hole transport layer; if the first carrier transport layer is a hole transport layer, then the second carrier transport layer is an electron transport layer.

[0020] It should be noted that the material of the electron transport layer is not limited in this invention; for example, it can be C. 60 The materials used in this invention include PCBM, TiO2, SnO2, ZnO, or ZnO-ZnS, etc. The material of the hole transport layer is not limited in this invention; exemplary examples include poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene (Spiro-OMeTAD), and poly(3,4-ethylenedioxythiophene:polyphenylene). Ethylene sulfonate (PEDOT:PSS), 4-butyl-N,N-diphenylaniline homopolymer (Ploy-TPD), polyvinylcarbazole (PVK), [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz), [3-(9H-carbazole-9-yl)ethyl]phosphonic acid (3PACz), [4-(9H-carbazole-9-yl)ethyl]phosphonic acid (4PACz), NiOx, CuI or CuSCN, etc.

[0021] Preferably, the chemical formula of the perovskite absorber layer is ABX3, where A is CH3NH3. + CH(NH2)2 + Cs + or Rb + B is any combination of one or at least two of the following, where B is Pb. 2+ Sn 2+ Or Ge 2+ Any combination of one or at least two of them, X is Cl - ,Br - or I - Any one or at least two of them.

[0022] Preferably, the thickness of the perovskite absorber layer is 300-700 nm, for example, it can be 300 nm, 400 nm, 500 nm, 600 nm or 700 nm.

[0023] In a second aspect, the present invention provides a method for preparing a perovskite solar cell as described in the first aspect, characterized in that the preparation method includes the following steps:

[0024] The perovskite solar cell is obtained by sequentially depositing a first carrier transport layer, a silver nanoparticle layer, a perovskite absorber layer, a second carrier transport layer, and an electrode layer on the surface of a substrate.

[0025] As a preferred embodiment of the present invention, the method for depositing the nano-silver particle layer includes the following steps:

[0026] A solution containing silver nanoparticles is coated onto the first carrier transport layer, and the silver nanoparticle layer is formed after annealing.

[0027] Preferably, the coating method includes any one or a combination of at least two of spin coating, blade coating, slot coating, or screen printing.

[0028] As a preferred embodiment of the present invention, the concentration of the solution containing silver nanoparticles is 1-5 mg / mL, for example, it can be 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL or 5 mg / mL, etc.

[0029] In this invention, if the concentration of the solution containing silver nanoparticles is too low, it cannot effectively improve the crystallization of the perovskite film, resulting in an insignificant increase in the size of the formed grains, a relatively poor quality of the film, and a decrease in battery efficiency. If the concentration of the solution containing silver nanoparticles is too high, the light-trapping structure formed cannot play its role well, resulting in a decrease in light utilization and thus affecting battery efficiency.

[0030] Preferably, the solvent of the solution containing silver nanoparticles is a polar solvent.

[0031] Preferably, the polar solvent includes any one or a combination of at least two of water, ethanol, methanol, or ethylene glycol.

[0032] Preferably, in the spin coating method, the spin coating rate of the solution containing silver nanoparticles is 4000-6000 rpm, for example, 4000 rpm, 5000 rpm or 6000 rpm, and the time is 40-50 s, for example, 40 s, 45 s or 50 s.

[0033] Preferably, the annealing temperature is 120-180℃, for example, 120℃, 130℃, 140℃, 150℃, 160℃, 170℃ or 180℃, and the time is 8-12 minutes, for example, 8 minutes, 9 minutes, 10 minutes, 11 minutes or 12 minutes.

[0034] In this invention, if the annealing temperature is too low, solvent residue will be left, which will affect the crystallization of the perovskite film in the next step; if the annealing temperature is too high, the end-capping agent structure on the surface of the silver cube will be destroyed, which will eventually cause the silver cube to be unstable.

[0035] As a preferred technical solution of the present invention, the silver nanoparticles in the solution containing silver nanoparticles are silver cubic nanoparticles.

[0036] The method for synthesizing the silver cube nanoparticles includes:

[0037] (a) A reducing agent solution, an acid solution, a protective agent solution, an Ag source solution, and a solvent are mixed and reacted. After the reaction is completed, the mixture is quenched to obtain a seed crystal solution.

[0038] (b) The seed solution, capping agent solution, silver precursor solution and reducing agent are mixed and reacted. After the reaction is completed, the reaction is quenched to obtain the silver cubic nanoparticles.

[0039] As a preferred technical solution of the present invention, the reducing agent solution in step (a) includes NaHS solution;

[0040] Preferably, the acid solution in step (a) includes a hydrochloric acid solution.

[0041] Preferably, the concentration of the acid solution in step (a) is 2-4 mmol / L, for example, it can be 2 mmol / L, 2.5 mmol / L, 3 mmol / L, 3.5 mmol / L or 4 mmol / L.

[0042] Preferably, the protective agent solution in step (a) comprises a polyvinylpyrrolidone solution.

[0043] Preferably, the concentration of the protective agent solution in step (a) is 2-4 mmol / L, for example, it can be 2 mmol / L, 2.5 mmol / L, 3 mmol / L, 3.5 mmol / L or 4 mmol / L.

[0044] Preferably, the Ag source solution in step (a) includes a CF3COOAg solution.

[0045] Preferably, the concentration of the Ag source solution in step (a) is 250-300 mmol / L, for example, it can be 250 mmol / L, 260 mmol / L, 270 mmol / L, 280 mmol / L, 290 mmol / L or 300 mmol / L, etc.

[0046] Preferably, the volume ratio of the reducing agent solution, acid solution, protective agent solution, and Ag source solution in step (a) is (0.04-0.08):(0.3-0.7):(1-1.5):(0.2-0.6), wherein the reducing agent solution is selected in the range of "0.04-0.08", for example, 0.04, 0.06, or 0.08; the acid solution is selected in the range of "0.3-0.7", for example, 0.3, 0.5, or 0.7; the protective agent solution is selected in the range of "1-1.5", for example, 1, 1.3, or 1.5; and the Ag source solution is selected in the range of "0.2-0.6", for example, 0.2, 0.4, or 0.6.

[0047] Preferably, the capping agent solution in step (b) comprises a polyvinylpyrrolidone solution.

[0048] Preferably, the concentration of the capping agent solution in step (b) is 15-25 mg / mL, for example, it can be 15 mg / mL, 20 mg / mL or 25 mg / mL.

[0049] Preferably, the silver precursor solution in step (b) comprises a silver nitrate solution.

[0050] Preferably, the concentration of the silver precursor solution in step (b) is 250-300 mmol / L, for example, it can be 250 mmol / L, 260 mmol / L, 270 mmol / L, 280 mmol / L, 290 mmol / L or 300 mmol / L.

[0051] Preferably, the reducing agent in step (b) includes ethylene glycol.

[0052] Preferably, the volume ratio of the seed solution, capping agent solution, silver precursor solution, and reducing agent in step (b) is (0.2-0.4):(0.2-0.4):(0.1-0.3):(1-1.5), wherein the seed solution is selected in the range of "0.2-0.4", for example, 0.2, 0.3, or 0.4; the capping agent solution is selected in the range of "0.2-0.4", for example, 0.2, 0.3, or 0.4; the protective agent solution is selected in the range of "0.1-0.3", for example, 0.1, 0.2, or 0.3; and the Ag source solution is selected in the range of "1-1.5", for example, 1, 1.3, or 1.5.

[0053] As a preferred technical solution of the present invention, the reaction temperature in step (a) is 130-170℃, for example, it can be 130℃, 140℃, 150℃, 160℃, 170℃, etc.

[0054] Preferably, the reaction temperature in step (b) is 130-170°C, for example, 130°C, 150°C or 170°C, and the reaction time is 20-40 min, for example, 20 min, 30 min or 40 min.

[0055] In this invention, the reducing agent ethylene glycol in step (b) can act as both a reducing agent and a solvent.

[0056] As a preferred technical solution of the present invention, the preparation method includes the following steps:

[0057] (1) Under stirring conditions, the reducing agent solution, acid solution, protective agent solution, Ag source solution and solvent are mixed and reacted at 130-170℃, followed by quenching to obtain a seed crystal solution;

[0058] The concentration of the reducing agent solution is 2-4 mmol / L, the concentration of the acid solution is 2-4 mmol / L, the concentration of the protective agent solution is 15-25 mg / mL, the concentration of the Ag source solution is 250-300 mmol / L, the solvent includes ethylene glycol, and the volume ratio of the reducing agent solution, acid solution, protective agent solution and Ag source solution is (0.04-0.08):(0.3-0.7):(1-1.5):(0.2-0.6).

[0059] (2) Under stirring conditions, the seed solution, capping agent solution, silver precursor solution and reducing agent are mixed and reacted at 130-170℃. After the reaction is quenched for 20-40 minutes, the silver cubic nanoparticles can be obtained.

[0060] The concentration of the capping agent solution is 15-25 mg / mL, the concentration of the silver precursor solution is 250-300 mmol / L, the reducing agent includes ethylene glycol, and the volume ratio of the seed solution, capping agent solution, silver precursor solution and reducing agent is (0.2-0.4):(0.2-0.4):(0.1-0.3):(1-1.5).

[0061] (3) An electron transport layer is deposited on the surface of a transparent conductive glass, and then a solution containing the silver cubic nanoparticles with a concentration of 1-5 mg / mL is spin-coated, followed by annealing to form a layer of silver nanoparticles.

[0062] The spin coating rate is 4000-6000 rpm, the time is 40-50 s, the annealing temperature is 120-180℃, and the time is 8-12 min.

[0063] (4) A perovskite absorber layer, a hole transport layer and an electrode layer are sequentially deposited on the nano-silver particle layer to obtain the perovskite solar cell.

[0064] It should be noted that the quenched ethanol solution can be reused after centrifugation and washing.

[0065] Thirdly, the present invention provides a photovoltaic module, the photovoltaic module comprising the perovskite solar cell as described in the first aspect.

[0066] The numerical range described in this invention includes not only the point values ​​listed above, but also any point values ​​within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values ​​included in the range.

[0067] Compared with the prior art, the present invention has the following beneficial effects:

[0068] This invention uses a layer of silver nanoparticles as crystal nuclei to promote the crystallization of the perovskite absorber layer, forming a high-quality perovskite thin film with large grain size and low defect density. Furthermore, the surface of the silver nanoparticles can reflect sunlight, forming a light-trapping structure that significantly improves light utilization. In summary, this invention can effectively improve the photoelectric performance of perovskite solar cells and has broad application prospects. Attached Figure Description

[0069] Figure 1 This is a schematic diagram of the structure of the perovskite solar cell provided in Embodiment 1 of the present invention.

[0070] Figure 2 This is a diagram illustrating the light utilization mechanism of the silver cubic nanoparticle layer in Example 1 of the present invention.

[0071] Figure 3 The UV-Vis absorption spectra of the seed crystals and silver cubic nanoparticles provided in Example 1 of this invention are shown.

[0072] Figure 4 The images are TEM images of the silver cube nanoparticles provided in Example 1 of this invention at different magnifications.

[0073] Figure 5 The image shows a comparison of the ultraviolet-visible absorption spectra of the perovskite-containing layer samples prepared in Examples 1, 4-5 and Comparative Example 1 of this invention.

[0074] Figure 6The images show a comparison of the fluorescence spectra of perovskite-containing layer samples prepared in Examples 1, 4-5, and Comparative Example 1 of this invention.

[0075] Figure 7 Stability comparison chart of perovskite solar cells prepared in Examples 1, 4-5, 11-12 and Comparative Example 1 of this invention.

[0076] Among them, 1-transparent conductive glass; 2-electron transport layer; 3-silver nanoparticle layer; 4-perovskite absorption layer; 5-hole transport layer; 6-metal electrode. Detailed Implementation

[0077] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0078] Example 1

[0079] This embodiment provides a perovskite solar cell, the structural schematic of which is shown below. Figure 1 As shown, the perovskite solar cell includes a transparent conductive glass 1, an electron transport layer 2, a perovskite absorber layer 4, a hole transport layer 5, and a metal electrode 6 stacked sequentially. A layer of silver nanoparticles 3 is disposed between the electron transport layer 3 and the perovskite absorber layer 4.

[0080] The silver nanoparticle layer 3 is a silver cubic nanoparticle layer with a side length of 50 nm and a thickness of 100 nm.

[0081] The transparent conductive glass 1 is ITO conductive glass;

[0082] The electron transport layer 2 is a TiO2 layer with a thickness of 300 nm;

[0083] The chemical formula of the perovskite absorber layer 4 is FA. 0.95 MA 0.05 PbI3, with a thickness of 550 nm;

[0084] The hole transport layer 5 is a Spiro-OMeTAD layer with a thickness of 250 nm;

[0085] The metal electrode 6 is a gold electrode with a thickness of 80 nm.

[0086] This embodiment also provides a method for preparing the above-mentioned perovskite solar cell, the method comprising the following steps:

[0087] (1) Under the conditions of magnetic stirring at 300 rpm and oil bath temperature of 150 ℃, 10 mL of ethylene glycol was added to a 50 mL round bottom flask, followed by 0.06 mL of reducing agent solution. After 2 min, 0.5 mL of acid solution and 1.25 mL of protective agent solution were added. After 2 min, 0.4 mL of Ag source solution was added. The reaction was stopped when the solution turned dark green. Then, the reaction was quenched in ice-cold ethanol solution to obtain seed crystal solution.

[0088] The reducing agent solution is a 3 mmol / L NaHS solution, the acid solution is a 3 mmol / L hydrochloric acid solution, the protective agent solution is a 20 mg / mL polyvinylpyrrolidone solution, and the Ag source solution is a 282 mmol / L CF3COOAg solution. The volume ratio of the reducing agent solution, acid solution, protective agent solution, and Ag source solution is 0.06:0.5:1.25:0.4.

[0089] (2) Under the conditions of magnetic stirring at 300 rpm and oil bath temperature of 150 ℃, 1.25 mL of reducing agent was placed in a 20 mL glass bottle. After 1.5 min, 0.3 mL of capping agent solution was added, and after 1.5 min, 0.3 mL of seed crystal solution was added. Then, 0.2 mL of silver precursor solution was added. After reacting for 30 min, heating was stopped, and the mixture was placed in an ice-cold ethanol solution for quenching to obtain the silver cubic nanoparticles.

[0090] Wherein, the capping agent solution is a polyvinylpyrrolidone solution with a concentration of 20 mg / mL, the silver precursor solution is a silver nitrate solution with a concentration of 282 mmol / L, the reducing agent is ethylene glycol, and the volume ratio of the seed solution, capping agent solution, silver precursor solution and reducing agent is 0.3:0.3:0.2:1.25;

[0091] (3) Clean the ITO conductive glass, specifically by ultrasonic cleaning with detergent, deionized water, acetone and anhydrous ethanol respectively, and then drying it with a nitrogen gun.

[0092] The ultrasonic cleaning power was 100Hz, and the ultrasonic cleaning time was 15min.

[0093] (4) Depositing a TiO2 layer on the surface of the ITO conductive glass, specifically including:

[0094] 2 mL of ethanol was placed in a flask, and 0.5 mL of titanium tetrachloride was added dropwise under stirring. Then, 10 mL of anhydrous benzyl alcohol was added to obtain a yellow transparent solution. The solution was then stirred in a water bath at 80°C for 8 hours to form a milky-colored suspension. 200 mL of diethyl ether solution was added to the suspension, and the mixture was centrifuged at 8000 rpm for 10 min to obtain a precipitate. The precipitate was dissolved in 30 mL of anhydrous ethanol, and then centrifuged in 200 mL of diethyl ether at 8000 rpm for 10 min to precipitate the precipitate. This process was repeated three times. After the precipitation, the obtained titanium oxide nanoparticles were washed. The washed titanium oxide nanoparticles were dispersed in an ethanol solution to obtain a TiO2 solution with a concentration of 6 mg / mL.

[0095] TiO2 solution was dropped onto the surface of ITO conductive glass, spin-coated at 3000 rpm for 25 seconds, and then annealed at 125℃ for 10 minutes to obtain TiO2 layer.

[0096] (5) Take 80 μL of ethanol solution containing silver cubic nanoparticles and spin-coat it on the surface of TiO2 layer. The spin-coating speed is 5000 rpm and the time is 45 s. Then anneal at 150℃ for 10 min to form a silver cubic nanoparticle layer.

[0097] The concentration of the ethanol solution containing silver cube nanoparticles was 2 mg / mL.

[0098] (6) Preparation of the perovskite absorber layer 4, the specific steps of which include:

[0099] MAI, FAI, MACl, and PbI2 were dissolved in a mixed solvent consisting of dimethyl sulfoxide and dimethylformamide in a volume ratio of 1:9. The mixture was heated at 70°C and stirred continuously for 1 hour to obtain a perovskite precursor solution. In the perovskite precursor solution, the concentration ratio of FAI:MAI:MACl was 0.95:0.05:0.14, and the concentrations of FAI and PbI2 were both 1.5 mol / L.

[0100] The perovskite precursor solution was spin-coated onto the silver cubic nanoparticle layer at a speed of 5000 rpm for 50 s, followed by annealing at 120 °C for 15 min to obtain the product with the chemical formula FA. 0.95 MA 0.05 4. PbI3 perovskite absorber layer;

[0101] (7) Preparation of the Spiro-OMeTAD layer, the specific steps of which include:

[0102] Prepare a 520 mg / mL lithium bis(trifluoromethanesulfonyl)imide solution in acetonitrile. Then, dissolve 72.3 mg of Spiro-OMeTAD powder, 28.8 μL of 4-tert-butylpyridine solution, and 17.5 μL of lithium bis(trifluoromethanesulfonyl)imide solution in 1 mL of chlorobenzene and stir to obtain the Spiro-OMeTAD solution.

[0103] 1 mL of the Spiro-OMeTAD solution was spin-coated onto the surface of the perovskite absorber layer at a speed of 5000 rpm for 30 s to obtain the Spiro-OMeTAD layer.

[0104] (8) Fabrication of gold electrodes on the surface of the Spiro-OMeTAD layer:

[0105] The prepared sample was placed on the mask plate of the coating machine, and the gold raw material was thermally evaporated. The vacuum degree in the evaporation chamber was 1.0 × 10⁻⁶. -4 Pa, evaporation rate is After completion, perovskite solar cells were obtained.

[0106] Figure 2 The diagram shows the light utilization mechanism of the silver cubic nanoparticle layer prepared in this embodiment. As can be seen from the diagram, the surface of the silver cubic nanoparticles can reflect sunlight, forming a light-trapping structure and improving the light utilization rate.

[0107] Figure 3 The UV-Vis absorption spectra of the seed crystals and silver cubic nanoparticles in the seed solution provided in this embodiment are shown. As can be seen from the figure, the absorption peak of the perovskite film after treatment with silver cubic nanoparticles shows a slight red shift. This is mainly because silver cubic nanoparticles can effectively improve the crystallization of the perovskite film and form larger grains.

[0108] Figure 4 The TEM images of the silver cubic nanoparticles provided in this embodiment at different magnifications are shown. The left image is at 120,000x magnification and the right image is at 1,200,000x magnification. As can be seen from the images, the silver nanoparticles prepared in this embodiment have a side length of 50 nm.

[0109] Example 2

[0110] The difference between this embodiment and embodiment 1 is that step (5) includes the following specific steps:

[0111] Take 80 μL of ethanol solution containing silver cubic nanoparticles and spin-coat it on the surface of TiO2 layer at a speed of 6000 rpm for 40 s. Then anneal at 180 °C for 8 min to form a silver cubic nanoparticle layer.

[0112] The concentration of the ethanol solution containing silver cube nanoparticles was 3 mg / mL.

[0113] The remaining preparation methods and parameters are consistent with those in Example 1.

[0114] Example 3

[0115] The difference between this embodiment and embodiment 1 is that step (5) includes the following specific steps:

[0116] Take 80 μL of ethanol solution containing silver cubic nanoparticles and spin-coat it on the surface of TiO2 layer at a speed of 4000 rpm for 50 s. Then anneal at 120 °C for 12 min to form a silver cubic nanoparticle layer.

[0117] The concentration of the ethanol solution containing silver cube nanoparticles was 4 mg / mL.

[0118] The remaining preparation methods and parameters are consistent with those in Example 1.

[0119] Example 4

[0120] The difference between this embodiment and Embodiment 1 is that the concentration of the ethanol solution containing silver cubic nanoparticles in step (5) is 1 mg / mL.

[0121] The remaining preparation methods and parameters are consistent with those in Example 1.

[0122] Example 5

[0123] The difference between this embodiment and Embodiment 1 is that the concentration of the ethanol solution containing silver cubic nanoparticles in step (5) is 5 mg / mL.

[0124] The remaining preparation methods and parameters are consistent with those in Example 1.

[0125] Example 6

[0126] The difference between this embodiment and embodiment 1 is that the side length of the silver cube nanoparticle layer is 100 nm by adjusting the parameters in step (5).

[0127] The remaining preparation methods and parameters are consistent with those in Example 1.

[0128] Example 7

[0129] The difference between this embodiment and embodiment 1 is that the side length of the silver cube nanoparticle layer is 10 nm by adjusting the parameters in step (5).

[0130] The remaining preparation methods and parameters are consistent with those in Example 1.

[0131] Example 8

[0132] The difference between this embodiment and embodiment 1 is that the side length of the silver cube nanoparticle layer is 150 nm by adjusting the parameters in step (5).

[0133] The remaining preparation methods and parameters are consistent with those in Example 1.

[0134] Example 9

[0135] The difference between this embodiment and embodiment 1 is that the side length of the silver cube nanoparticle layer is 5nm by adjusting the parameters in step (5).

[0136] The remaining preparation methods and parameters are consistent with those in Example 1.

[0137] Example 10

[0138] The difference between this embodiment and embodiment 1 is that the side length of the silver cube nanoparticle layer is 200 nm by adjusting the parameters in step (5).

[0139] The remaining preparation methods and parameters are consistent with those in Example 1.

[0140] Example 11

[0141] The difference between this embodiment and Embodiment 1 is that the concentration of the ethanol solution containing silver cubic nanoparticles in step (5) is 0.5 mg / mL.

[0142] The remaining preparation methods and parameters are consistent with those in Example 1.

[0143] Example 12

[0144] The difference between this embodiment and embodiment 1 is that the concentration of the ethanol solution containing silver cubic nanoparticles in step (5) is 7 mg / mL.

[0145] The remaining preparation methods and parameters are consistent with those in Example 1.

[0146] Example 13

[0147] The difference between this embodiment and embodiment 1 is that the annealing temperature in step (5) is 100°C.

[0148] The remaining preparation methods and parameters are consistent with those in Example 1.

[0149] Example 14

[0150] The difference between this embodiment and embodiment 1 is that the annealing temperature in step (5) is 200°C.

[0151] The remaining preparation methods and parameters are consistent with those in Example 1.

[0152] Comparative Example 1

[0153] The difference between this comparative example and Example 1 is that the silver cubic nanoparticle layer is not set, that is, step (5) is not performed.

[0154] The remaining preparation methods and parameters are consistent with those in Example 1.

[0155] Figure 5 The violet-visible absorption spectra of the perovskite layer samples prepared in Examples 1, 4-5 and Comparative Example 1 are shown in the figure. As can be seen from the figure, the absorption peak of the perovskite layer after treatment with silver cubic nanoparticles has a slight red shift. This is mainly because silver cubic nanoparticles can effectively improve the crystallization quality of the perovskite layer and form larger grains.

[0156] Figure 6 The fluorescence spectra of the perovskite layer samples prepared in Examples 1, 4-5 and Comparative Example 1 are shown in the figure. As can be seen from the figure, the emission peak of the fluorescence spectrum of the perovskite layer after treatment with silver cube nanoparticles is significantly improved, indicating that the defects of the perovskite layer after treatment are reduced, and also proving that the quality of perovskite film formation is improved.

[0157] Figure 7 The efficiency changes of perovskite solar cells prepared in Examples 1, 4-5, 11-12 and Comparative Example 1 after encapsulation and placement in a nitrogen glove box for 1000 hours are shown. As can be seen from the figure, the stability of the perovskite solar cells treated with silver cubic nanoparticles can still maintain more than 90% of the initial value after 1000 hours, while the untreated solar cells decay faster. This indicates that the treated cells not only have improved efficiency but also improved stability.

[0158] Performance testing

[0159] The photoelectric performance of the perovskite solar cells prepared in the above embodiments and comparative examples was tested under the following conditions: AM1.5, 1000 W / m 2 , 25±2℃.

[0160] The test results are shown in Table 1.

[0161] Table 1

[0162]

[0163]

[0164] analyze:

[0165] As shown in the table above, the perovskite solar cells fabricated by introducing silver cube nanoparticles exhibit significantly improved open-circuit voltage, short-circuit current, fill factor, and photoelectric conversion efficiency.

[0166] As demonstrated in Examples 1 and 6-10, a suitable size of the silver cubic nanoparticle layer can effectively improve the crystallinity of the perovskite thin film, resulting in a perovskite solar cell with excellent performance. If the size is too small, it cannot effectively promote the crystallization of the perovskite thin film, leading to a decrease in efficiency; if the size is too large, it will affect the extraction of charge carriers inside the cell, thereby affecting the cell efficiency.

[0167] As can be seen from Examples 1 and 11-12, if the concentration is too low, it cannot effectively improve the crystal quality of the perovskite film, resulting in an insignificant increase in the size of the formed grains, a relatively poor quality of the film, and a decrease in battery efficiency; if the concentration is too high, the light-trapping structure formed cannot play its role well, resulting in a decrease in light utilization, which in turn affects battery efficiency.

[0168] As can be seen from Examples 1 and 13-14, if the annealing temperature is too low, solvent residue will be left, which will affect the crystallization of the perovskite film in the next step and reduce the battery efficiency; if the annealing temperature is too high, the end-capping agent structure on the surface of the silver cube will be destroyed, which will eventually cause the silver cube to be unstable and the battery efficiency to be poor.

[0169] As can be seen from Example 1 and Comparative Example 1, if the silver cubic nanoparticle layer is not provided, the crystal quality of the perovskite film is poor and the light utilization rate cannot be significantly improved, resulting in a significant decrease in the efficiency of the battery.

[0170] The applicant declares that the present invention is illustrated by the above embodiments, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A perovskite solar cell, characterized in that, The perovskite solar cell includes a substrate, a first carrier transport layer, a perovskite absorber layer, a second carrier transport layer, and an electrode layer stacked sequentially, with a layer of silver nanoparticles disposed between the first carrier transport layer and the perovskite absorber layer.

2. The perovskite solar cell according to claim 1, characterized in that, The nano-silver particle layer comprises silver cubic nanoparticles; Preferably, the side length of the silver cubic nanoparticles is 10-150 nm; Preferably, the thickness of the silver nanoparticle layer is 10-300 nm.

3. The perovskite solar cell according to claim 1 or 2, characterized in that, The first carrier transport layer and the second carrier transport layer transport carriers of opposite types; Preferably, the chemical formula of the perovskite absorber layer is ABX3, where A is CH3NH3. + CH(NH2)2 + Cs + or Rb + B is any combination of one or at least two of the following, where B is Pb. 2+ Sn 2+ Or Ge 2+ Any combination of one or at least two of them, X is Cl - ,Br - Or I - Any one or at least two of them; Preferably, the thickness of the perovskite absorber layer is 300-700 nm.

4. A method for preparing a perovskite solar cell according to any one of claims 1-3, characterized in that, The preparation method includes the following steps: The perovskite solar cell is obtained by sequentially depositing a first carrier transport layer, a silver nanoparticle layer, a perovskite absorber layer, a second carrier transport layer, and an electrode layer on the surface of a substrate.

5. The preparation method according to claim 4, characterized in that, The method for depositing the nano-silver particle layer includes the following steps: A solution containing silver nanoparticles is coated onto the first carrier transport layer, and the silver nanoparticle layer is formed after annealing.

6. The preparation method according to claim 5, characterized in that, The concentration of the solution containing silver nanoparticles is 1-5 mg / mL; Preferably, the solvent of the solution containing silver nanoparticles is a polar solvent; Preferably, the polar solvent includes any one or a combination of at least two of water, ethanol, methanol, or ethylene glycol; Preferably, the annealing temperature is 120-180℃ and the time is 8-12 minutes.

7. The preparation method according to claim 5 or 6, characterized in that, In the solution containing silver nanoparticles, the silver nanoparticles are silver cubic nanoparticles. The method for synthesizing the silver cube nanoparticles includes: (a) A reducing agent solution, an acid solution, a protective agent solution, an Ag source solution, and a solvent are mixed and reacted. After the reaction is completed, the mixture is quenched to obtain a seed crystal solution. (b) The seed solution, capping agent solution, silver precursor solution and reducing agent are mixed and reacted. After the reaction is completed, the reaction is quenched to obtain the silver cubic nanoparticles.

8. The preparation method according to claim 7, characterized in that, The reducing agent solution in step (a) includes a NaHS solution; Preferably, the protective agent solution in step (a) comprises a polyvinylpyrrolidone solution; Preferably, the Ag source solution in step (a) comprises a CF3COOAg solution; Preferably, the capping agent solution in step (b) comprises a polyvinylpyrrolidone solution; Preferably, the silver precursor solution in step (b) comprises a silver nitrate solution; Preferably, the reducing agent in step (b) includes ethylene glycol.

9. The preparation method according to any one of claims 4-8, characterized in that, The preparation method includes the following steps: (1) Under stirring conditions, the reducing agent solution, acid solution, protective agent solution, Ag source solution and solvent are mixed and reacted at 130-170℃, followed by quenching to obtain a seed crystal solution; The concentration of the reducing agent solution is 2-4 mmol / L, the concentration of the acid solution is 2-4 mmol / L, the concentration of the protective agent solution is 15-25 mg / mL, the concentration of the Ag source solution is 250-300 mmol / L, the solvent includes ethylene glycol, and the volume ratio of the reducing agent solution, acid solution, protective agent solution and Ag source solution is (0.04-0.08):(0.3-0.7):(1-1.5):(0.2-0.6). (2) Under stirring conditions, the seed solution, capping agent solution, silver precursor solution and reducing agent are mixed and reacted at 130-170℃. After the reaction is quenched for 20-40 minutes, the silver cubic nanoparticles can be obtained. The concentration of the capping agent solution is 15-25 mg / mL, the concentration of the silver precursor solution is 250-300 mmol / L, the reducing agent includes ethylene glycol, and the volume ratio of the seed solution, capping agent solution, silver precursor solution and reducing agent is (0.2-0.4):(0.2-0.4):(0.1-0.3):(1-1.5). (3) An electron transport layer is deposited on the surface of a transparent conductive glass, and then a solution containing the silver cubic nanoparticles with a concentration of 1-5 mg / mL is spin-coated, followed by annealing to form a layer of silver nanoparticles. The spin coating rate is 4000-6000 rpm, the time is 40-50 s, the annealing temperature is 120-180℃, and the time is 8-12 min. (4) A perovskite absorber layer, a hole transport layer and an electrode layer are sequentially deposited on the nano-silver particle layer to obtain the perovskite solar cell.

10. A photovoltaic module, characterized in that, The photovoltaic module includes a perovskite solar cell as described in any one of claims 1-3.

Citation Information

Cited By

  • Photoelectric field synergistically enhanced tin-based perovskite solar cell based on silver nanoparticle interface modification and preparation method thereof

    CN122294706A